Reality checks in Mozambique. 2nd Annual Report - Governance - Tvedten, Inge (ORGUT Consulting AB, 2012)
The Reality Checks are implemented between 2011- 2016, with fieldwork being carried out each year in the Districts of Cuamba, Majune and Lago in the Niassa Province. Sub-Team Leaders are Carmeliza Rosário, Minna Tuominen and Inge Tvedten. This is the Annual Report for the 2nd Reality Check, synthesising the main findings from the three sub- reports. The report is written by the Team Leader for the Reality Checks in Mozambique Dr. Inge Tvedten - with support from Carmeliza Rosário, Minna Tuominen and Aslak Orre (Thematic Advisor).
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; gender / género; governance / governação; poverty / pobreza

Afrobarometer Round 5. Summary of Results for Mozambique, 2012 - Centro de Pesquisas de Governação e Desenvolvimento (CPGD) (Centro de Pesquisas de Governação e Desenvolvimento (CPGD), 2012)
The Afrobarometer is a comparative series of public attitude surveys that will be covering up to 35 African countries in Round 5 (2011-2013). Based on representative national samples, the surveys assess citizen attitudes to democracy and governance, markets, and civil society, among other topics. The first round of surveys was conducted between 1999-2001 and covered seven Southern African countries (Botswana, Lesotho, Malawi, Namibia, South Africa, Zambia and Zimbabwe), three countries in West Africa (Ghana, Nigeria and Mali) and two in East Africa (Uganda and Tanzania). Round 2 surveys were completed by November 2003 with four new countries added: Kenya, Senegal, Cape Verde and Mozambique. Round 3 surveys were conducted from March 2005 to February 2006 in the same countries, plus Benin and Madagascar. The 4th Round of surveys covered 20 countries between 2008 and 2009, with the addition of Burkina Faso and Liberia.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; civil society / sociedade civil; governance / governação